The Use of Foraminiferal Geochemistry to Investigate Methane Seepage at the Svyatogor Ridge, Arctic Ocean - Akinselure, Abidemi Alex (UiT Norges arktiske universitet, 2022)
Methane is a greenhouse gas contributing to contemporaneous global warming, and seepage is one of the ways through which it migrates from the deep sedimentary basins, all the way up to the hydro- and atmosphere. The study of methane seepage is still young as scientists are yet to discover most seep sites as well as seep associated biological species. A record of past methane seepage can be derived from the δ 13C stored in the foraminiferal tests and in the seafloor sediments via precipitation of carbonate minerals by microbial oxidation of methane. In this study, the stable isotopes of carbon and oxygen of the foraminiferal tests were used alongside sediment geochemistry and organic compounds of the sediment as proxies to investigate methane seepage at the Svyatogor Ridge, Arctic Ocean. Two lithological units were recognised from the gravity core (GC3), corresponding to different sedimentation patterns during the last deglaciation. 158 - 162 cm and 137 – 142 cm intervals of the gravity core were impacted by anaerobic oxidation of methane (AOM) processes based on the Ba/Ti peaks which represent barite fronts immediately above sulfate-methane transition zones (SMTZs). Also, the vertical shift in between the paleo-SMTZs shows an upward fluid flow. The paleo-SMTZs in the gravity core (GC3) formed later than 14.5 ca ka BP. The organic matter in the blade core (BlaC3) is highly depleted due to bacterial mat biomass which incorporated methane-derived carbon. The stable carbon and oxygen isotopes of the tests show that the foraminifera calcified under normal marine conditions and during the Younger Dryas post-Bølling period. The C/N (Carbon/Nitrogen) elemental ratios show a predominantly marine origin for the sedimentary organic matter with some mix of land-derived and marine-derived organic matter. The organic carbon concentration (%C) shows that the sediments are of low productivity. An interval rich in ice-rafted debris with bivalve shells associated with high C/N values was found at 120 to 140 cm interval in the ...